HPB P19 Our experience comparing multi-visceral and single organ excision of retroperitoneal sarcomas from a HPB centre. (7th December 2022) - Rehman, Adeeb; Rajput, Kunal; Kalaiselvan, Ramya; Jones, Robert; Diaz-Nieto, Rafael; Fenwick, Stephen; Malik, Hassan
Abstract: Background: Sarcomas are a heterogenous set of soft tissue cancers with an estimated incidence of up to 5.0 cases per 100, 00 worldwide. Retroperitoneal sarcomas (RPS) account for up to 20% of these. The aetiology behind the pathogenesis is not truly understood, but to date, surgery remains the only curative treatment. Owing to resistance, systemic chemotherapy only plays a role in attempts to downstage the tumour, or in the palliative setting. RPS are slow growing and owing to the lack of symptoms have variable presentation. The ability to excise RPS traditionally was limited by vascular invasion, which increases the complexity of the resection and poses uncertainty about the long-term oncological benefit. Although small, emerging case series over the last couple of decades have established the feasibility of multi-visceral resection with vascular reconstruction. Here we present our outcomes comparing multi-visceral resections with single organ resections with vascular reconstructions. Methods: All patients who underwent excision of a retroperitoneal sarcoma between January 2005 and April 2021 were included in the analysis. Patients were identified from a database which was prospectively completed by the operating surgeon. Data collected included patient demographics, clinicopathologic characteristics and intra-operative variables. Endpoints included perioperative morbidity and mortality, oncological clearance status, recurrence status, and survival. Complications were graded using the Clavien-Dindo classification. All patients were discussed in a local multi-disciplinary team meeting. When aortic/iliac artery involvement was suspected on pre-operative imaging (Computer Tomography or Magnetic Resonance Imaging), patients were referred appropriately to vascular for further pre-operative discussion regarding treatment and/or conduit plans. Continuous data was presented as medians (range) and compared using ANOVA (analysis of variance). Survival probabilities were calculated using the Kaplan-Meier method and log-rank test. Normally distributed data was assessed with the Student's t-test, and skewed data with Mann-Whitney test. A two-sided p value < 0.05 was considered significant. Results: From January 2005 to April 2021, 122 patients underwent 170 operations for RPS resections. 112 (68.9%) underwent a visceral resection (90 (53.0%) multi-visceral (MVR) and 22 (15.9%) single organ (SOR)). In the MVR group, 23 (25.6%) involved a synchronous vascular resection with a complete resection margin in 94.7%. In the SOR group, 6 (27.3%) underwent a synchronous vascular resection with a 96.3% complete resection margin. Multi-visceral resections included 39 nephrectomies, 33 segmental colectomies, 16 liver resections, 16 splenectomies, pancreatic resections in 19, and partial gastrectomy in 12 cases. The inferior vena cava was resected in 17 and 5 cases in the MVR and SOR group, respectively. Aortic and iliac artery resection and reconstruction with Dacron graft took place in 4 cases. Histologically, leiomyosarcomas and dedifferentiated liposarcomas were the most common subtype, accounting for 33 and 30 (36.7% and 33.3%) in the MVR group and 10 and 6 (37.0% and 22.2%) in the SOR group, respectively. Overall 5-year survival for all resections was 60%. There was no significant difference in complication rate[HM1] [AR2], length of stay, 30-day mortality (2% and 1%) or 1- (71.1% and 77.8%) or 3-year (33.3% and 25.9%) survival between the MVR and SOR groups. Conclusions: RPS are prone to localised invasion as well as into surrounding viscera. Although traditionally, these patients may not have been deemed suitable for surgical intervention, our case series shows multi-visceral resections with vascular resections can be undertaken safely with no impact on overall survival. The series also highlights the need for a multi-disciplinary surgical approach to address the technical complexities of the operation. In conclusion, the need for multi-visceral resection or vascular resection and reconstruction should not deter surgical treatment, and these cases should be managed within a MDT with appropriate surgical expertise.